Introducing environment management system within construction sites - Zakaria, Siti Fairus (2005)
Public awareness on the fragility of the environment and the increasing need to protect environmental quality has been growing in Malaysia since the Third Malaysian Plan. Thus, those involved in the development of many new projects (proponents, designers, constructors and operators) have to accept the responsibility along with the legal obligation for environmental management and actions. Additionally, the web of regulations woven in the last three decades have tended to increase the implementation of comprehensive environmental management to avoid costly mistakes, delays or even to the extend of project cancellation. The aim of the study is to introduce Environmental Management System (EMS) within construction sites. The basic concept of environmental management is explored and the detail site environmental management procedures are explained. The levels of awareness and understanding of EMS among the construction players are also investigated throughout of the study. Identification of the improvement and the action plans to reduce the impacts on the environment are established through the pattern shows by the questionnaire survey to the project engineers on construction sites. The survey components for the study are the project engineers of the construction projects in the Department of Irrigation and Drainage (DID) within year 1999 to 2003. Statistical analysis was performed on the data collected and the results were used to formulate the conclusion of the study. The study also highlights the findings that could be used to introduce environmental management system within construction sites. The study concludes that construction players should work towards introducing EMS within construction sites. The recommended approach and action plan listed are useful to construction practitioners to manage EMS processes and assess their performance towards continual environmental improvement while continuing project development with success.